Peran Komitmen Organisasional dalam Memediasi Pengaruh Kepuasan Kerja terhadap OCB Islam (Studi pada BMT Maslahah Sidogiri) - Yulianto, Nur Ahmad Budi; Noermijati, Noermijati; Sudiro, Achmad (Universitas Brawijaya, Indonesia, 2016)
Human role in an organization is a very important asset that must be managed effectively, because of their uniqueness in the human resources are diverse and constantly evolving, so that the problem of human resources is also more complicated. In Indonesia the human resource problems that often occur is a job satisfaction. Workers demonstrated to demand a wage increase for reasons workload is not balanced with the remuneration given by the company.This study aimed to determine the effect of job satisfaction and organizational commitment to Islamic Organizational Citizenship Behavior (OCB). This study is a quantitative study with explanatory research approach performed in BMT Maslahah Pasuruan. The population of this research is all employees of BMT Maslahah totaling 46 employees and the sample of this study were40 employees. The analysis methodis Partial Least Square (PLS) that is a tool of analysis using WarPLS 3.0. The results showed that job satisfaction has an effect on the Islamic OCB, satisfaction has an effect on the organizational commitment, OCB organizational commitment has an effect on the Islam, and organizational commitment mediated the effect of job satisfaction to theIslamic OCB.Â